(untitled) (Journal of Science and Technology, 2015)
This paper presents charts for the design of recuperators as an alternative to the heat exchanger design chart developed by the author in a previous paper (Ref. 2). The charts portray the relations between the Heat Exchanger Effectiveness and other basic design parameters